2005
DOI: 10.1111/j.1468-1331.2004.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI in late‐onset multiple sclerosis

Abstract: Multiple sclerosis (MS) with clinical onset after 50 years of age is unusual (between 1 and 6%) and is frequently misdiagnosed. Furthermore, brain magnetic resonance imaging (MRI) abnormalities are frequently observed in subjects over 50 years of age. The aim of this study was to describe brain MRI in late-onset MS to evaluate the sensitivity and specificity of radiological MS criteria in patients aged over 50 years. We evaluated the brain MRI of 20 patients with onset of MS after 50 years of age. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
3
17
2
Order By: Relevance
“…We observed that 50% of the 12 LOMS patients submitted to spinal MRI had lesions, thus helping to differentiate between MS and vascular diseases 11,14,18 . Our study demonstrated that spinal MRI may be a helpful diagnostic tool only in the primary progressive LOMS group, in which we found 75% of clusters with lesions shown in spinal MRI, a high percentage, as expected in this clinical course 6,11,18 . Clearly, there are limitations to our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We observed that 50% of the 12 LOMS patients submitted to spinal MRI had lesions, thus helping to differentiate between MS and vascular diseases 11,14,18 . Our study demonstrated that spinal MRI may be a helpful diagnostic tool only in the primary progressive LOMS group, in which we found 75% of clusters with lesions shown in spinal MRI, a high percentage, as expected in this clinical course 6,11,18 . Clearly, there are limitations to our study.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, an uncommon form of MS is one in which symptoms start at 50 plus years of age, called late onset multiple sclerosis (LOMS) 1,2,3,4,5,6,7,8 . It accounts for 1.4% to 9.9% of the MS population in different countries 2,4,5,7,9,10,11,12 .…”
mentioning
confidence: 99%
“…Symptoms of LOMS, such as fatigue or walking disturbance, can also be mistaken for signs of normal aging. Moreover, on MRI scan of the brain, physicians may attribute the white matter damage to blood vessel disease .…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a diagnosis of MS can be more difficult in older adults because white matter lesions due to small-vessel cerebrovascular disease are frequently found on brain MRI. 7,37 In this situation a stringent interpretation of brain MRI criteria for MS is mandatory and spinal cord MRI is helpful since spinal cord lesions do not occur with healthy aging. 11…”
Section: Ms In Older Adultsmentioning
confidence: 99%